Dare to defy the challenges of online business. (13th April 2020) - Jain, Ruchi; Khandelwal, Ruchi
The innerwear industry is one of the less researched businesses in India and is dealt as niche vertical of apparel industry. For the yesteryear's customers, buying innerwear was a covert and backroom affair but globalisation, internet and bright entrepreneurial ideas have changed the trajectory. Taking leverage of changing industry dynamics, a budding entrepreneur – Pallavi Khandelwal dared to step into this less explored territory. She banked upon her entrepreneurial skills and strategic decision-making for creating an identity through her internet-based startup to optimise the opportunity and defy the challenges of online business arena. The case serves as the setup to elaborate the aspirations and obstacles confronted by a budding entrepreneur. It provides perfect background to understand how strategic options, resource requirements and critical success factors (CSFs) undergo transformation with the different stages of business life cycle. Industry analysis conducted through references gathered from various reports by business consultancies, industry players, and whitepapers written on this field accompanied an in-depth personal interview with the protagonist Pallavi Khandelwal for establishing facts and data used in the case. Literature review and academic experience of authors are steered to establish the theoretical underpinning of the case.